Determining the Trade Value of Indonesian Lobster Exports to Destination Countries in 2018–2023 - Hotijah, Dini Siti; Faridatussalam, Sitti Retno (Yayasan Riset dan Pengembangan Intelektual, 2025)
Indonesia has a very wide water area, making it one of the countries with great potential in developing the fisheries industry, especially in leading commodities such as lobster. This study was conducted to examine various factors that impact the value of Indonesian lobster exports to six major trading partner countries, namely China, Hong Kong, Japan, Singapore, Malaysia, and South Korea throughout 2018 to 2023. This study uses several independent variables including lobster prices, consumption tastes (Ratio), GDP per capita of destination countries, export value (FOB), export quantity, and economic distance. This study uses a quantitative approach by utilizing secondary data in the form of panel data, consisting of a time series from 2018 to 2023 and cross-country data for six export destination countries. Information was obtained from official sources such as BPS, Trade Economic, World Bank, and the Ministry of Marine Affairs and Fisheries (KKP). Based on the results of the analysis, the Common Effect Model (CEM) approach was identified as the most appropriate model in this study compared to other approaches. The results of the F test show that all independent variables have a significant influence on the value of Indonesian lobster exports, both simultaneously and partially. The determination value (R²) of 65.94% indicates that the regression model is able to explain most of the variation in the value of lobster export trade. The results of this study play a significant role in supporting the formulation of policies to increase the competitiveness of Indonesian fishery exports in the international market.